CTA in Emergent Cardiovascular Care - Mosley, Mary (MD Conference Express, 2014)
Next to the established indications for computed tomography in aortic dissection and pulmonary embolism, coronary computed tomography angiography can reliably detect and rule out coronary artery stenosis when it is expertly performed in selected, well-prepared patients presenting with acute chest pain to the emergency department. Supporting data for its use and considerations for patient selection and obtaining acceptable images is discussed in this article.